MicroRNAs in the Intracellular Space, Regulation of Organelle Specific Pathways in Health and Disease - T. Nguyen, Thao; W. Brenu, Ekua; R. Staines, Don; M. Marshall-Gradisnik, Sonya (MicroRNA, 2014)
MicroRNAs (miRNA) are small ( 22 nucleotide] non-coding RNA molecules originally characterised as nonsense or junk DNA. Emerging research suggests that these molecules have diverse regulatory roles in an array of molecular, cellular and physiological processes. MiRNAs are versatile and highly stable molecules, therefore, they are able to exist as intracellular or extracellular miRNAs. The purpose of this paper is to review the function and role of miRNAs in the intracellular space with specific focus on the interactions between miRNAs and organelles such as the mitochondria and the rough endoplasmic reticulum. Understanding the role of miRNAs in the intracellular space may be vital in understanding the mechanism of certain diseases.
Keywords: miRNA